Consumer Response Analysis to Duri Durian Cake from Durian Seed Flour - Islam, Muhammad Fajrul (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2022)
This study aims to determine the method of making durian thorn cake with flour substituted for wheat flour to find out how the respondent's preference for durian thorn cake from durian seed flour is from the aspect of aroma, colour, texture and taste. This research method is a type of qualitative experimental research. The research location is STP AMPTA Yogyakarta. The population of this study were cookie producers and students of STP AMPTA Yogyakarta, with a sample of 15 panellists. The data collection method in this research is primary data and secondary data. And the data analysis method of this research is a hedonic test or preference test with Microsoft Excel program. The results of this study indicate that the aroma indicator has an average of 4.46 and a percentage of 89.33% with the criteria of very like, the colour indicator has an average of 4.13 and a percentage of 82.67% with the criteria of liking, the texture indicator has an average of 4.33 and the percentage 86.67% with criteria like very much and the taste indicator has a mean of 4.33 and a percentage of 83.33% with criteria like. So it can be concluded that respondents like durian thorn cake with durian seed flour in terms of aroma, colour, texture and taste.